2005
DOI: 10.2527/2005.83189x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate-induced apoptosis and cell cycle arrest in bovine kidney epithelial cells: Involvement of caspase and proteasome pathways1

Abstract: Beyond their nutritional effect, short-chain fatty acids, especially butyrate, modulate cell differentiation, proliferation, motility, and in particular, they induce cell cycle arrest and apoptosis. A bovine kidney epithelial cell line (Madin-Darby bovine kidney; MDBK) was used to investigate the cell cycle regulatory and apoptotic effects of butyrate. Butyrate not only induced apoptosis but also induced cell cycle arrest at the G1/S boundary and M/G2 in MDBK cells (P < 0.01). The cell responses were concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 34 publications
3
109
0
Order By: Relevance
“…Indeed, the intake of probiotics in feed can enhance calcium absorption by increasing the gene expression of monocarboxylate transport 1 and chloride channel calcium activated 5 (Shima et al, 2008). It was previously reported that sodium butyrate induces cell cycle arrest in MDBK cell and blocks DNA replication (Li and Elsasser, 2005). Genes associated with cyclins, cylin-dependent kinases, histone deacetylase, helicases, chromosomal structure proteins and kinesins are downregulated in MDBK cells after treatment with sodium butyrate (Li and Li, 2006).…”
Section: Group C Genusmentioning
confidence: 99%
“…Indeed, the intake of probiotics in feed can enhance calcium absorption by increasing the gene expression of monocarboxylate transport 1 and chloride channel calcium activated 5 (Shima et al, 2008). It was previously reported that sodium butyrate induces cell cycle arrest in MDBK cell and blocks DNA replication (Li and Elsasser, 2005). Genes associated with cyclins, cylin-dependent kinases, histone deacetylase, helicases, chromosomal structure proteins and kinesins are downregulated in MDBK cells after treatment with sodium butyrate (Li and Li, 2006).…”
Section: Group C Genusmentioning
confidence: 99%
“…NaBu can cause cell blockage at the G1-phase of the cell cycle (Hendrick et al 2001;Kim and Lee 2002), inhibit histone deacetylases (Buckley et al 1996;Pikaart et al 1998;Cherlet and Marc 2000;Monneret 2005), induce cell differentiation (Garcia-Bermejo et al 1997) and apoptosis (Kim and Lee 2002). Two CDKs, cdc6 and cdk1, were down regulated in NaBu-mediated cell cycle arrested bovine kidney epithelial cells (MDBK) (Li and Elsasser 2005). Cdc6 has been shown to be rate limiting for initiation of DNA replication in a number of eukaryotic cell lines and is essential for the assembly of the prereplication complex (Sun et al 2002) while cdk1 helps in mitosis (Li and Elsasser 2005).…”
Section: (Ii) Cell Engineering Based Approachesmentioning
confidence: 99%
“…Two CDKs, cdc6 and cdk1, were down regulated in NaBu-mediated cell cycle arrested bovine kidney epithelial cells (MDBK) (Li and Elsasser 2005). Cdc6 has been shown to be rate limiting for initiation of DNA replication in a number of eukaryotic cell lines and is essential for the assembly of the prereplication complex (Sun et al 2002) while cdk1 helps in mitosis (Li and Elsasser 2005). Approximately 67% of HeLa cells and 54% of CHO accumulated in the G1-phase following NaBu treatment (Xue and Rao 1981;Hendrick et al 2001).…”
Section: (Ii) Cell Engineering Based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrate also has a multitude of cellular regulatory effects that modulate cell differentiation, proliferation, and motility primarily by acting as a histone deacetylase (HDAC) inhibitor. Our previous studies established that butyrate plays a role in inducing cell cycle arrest and apoptosis [2,3,4,5]. The biological endpoint of a 24h treatment by 10mM sodium butyrate was resultant death of approximately 38% of total cells, mainly due to apoptosis [2].…”
Section: Introductionmentioning
confidence: 99%